Decolorization of some azo dyes by direct photolysis and H2O2/UV processes. - Yassumoto, Lízia; Monezi, Natália Mariana; Takashima, Keiko (Semina: Ciências Exatas e Tecnológicas, 2009)
The decolorization of acid orange 7 (AO7), direct orange 34 (DO 34), direct red 23 (DR23) and direct yellow 86 (DY86) azo dyes was investigated by direct photolysis and hydrogen peroxide-assisted photodegradation respectively in closed and open reactor to the atmosphere under UV radiation at natural pHs and 30 ºC. Four azo dyes decolorization (1,5x10-4 mol L-1) was not significant in presence of H2O2 in closed reactor during 3 h irradiation, whereas in open reactor, the decolorization was respectively 96, 82, 32, and 45% for AO7, DO34, DR23 and DY86. The decolorization by direct photolysis in open reactor was significantly higher in comparison to closed one.